STUDI PENDAHULUAN : PERBANDINGAN MIKROBIOTA USUS PADA PASIEN KANKER SEBELUM DAN SETELAH DIBERIKAN ES KRIM PROBIOTIK PASKA KEMOTERAPI - iis Herawati; Ulima Nadiah; Rikahan Nurhasanah; Nurul Akidah; Riska Ananda Syafei; Rosi Sapitri (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Cancer is a disease that arises due to errors in the cell division system, resulting in abnormal cell growth, which can change shape and spread to other organs or metastasize. Chemotherapy is the mainstay of cancer treatment, but it can cause changes in the composition of the microbiota in the digestive tract. A decrease in microbiota can interfere with the protective effect against pathogen colonization, so it needs to be restored by consuming probiotics. This study aimed to compare stool consistency and probiotic bacteria counts in breast cancer patients undergoing chemotherapy before and after being given probiotic ice cream containing Lactobacillus acidophilus and Bifidobacterium longum. This was an experimental study that counted the bacteria before and after giving probiotic ice cream to the stool of nine breast cancer patients undergoing chemotherapy at the Cibabat Regional General Hospital in Cimahi City. The number of probiotic bacterial colonies in the patients' feces before and after consuming probiotic ice cream twice a day for 3 days was counted macroscopically on MRSA media. The results showed that the consistency of feces before treatment was 1 hard sample, 1 liquid sample, and 7 soft samples. After treatment, all samples had a soft consistency. There was an increase in the number of probiotic bacteria in 7 patients and a decrease in 2 patients. It was concluded that the administration of probiotic ice cream has the potential to increase the number of intestinal probiotics in breast cancer patients undergoing chemotherapy and improve stool consistency to normal.